Analisis Visual dan Wacana Kritis Lukisan 'Konoha 1' Yos Suprapto: Simbolisme Ketimpangan Kekuasaan di Indonesia" - Vivi Varlina; M. Ikhwan Apriansyah (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2025)
This article aims to analyse the symbols in Yos Suprapto's painting Konoha 1, which depicts power inequality and social injustice in Indonesia after the exhibition of this work was cancelled by the National Gallery of Indonesia in December 2024 because it was considered controversial. This study explores three main issues: 1) how visual symbolism in Konoha 1 reveals power hierarchies; 2) the socio-political messages embedded in such symbolism; and 3) how Norman Fairclough's critical discourse analysis can uncover the relationship between art and power in the Indonesian socio-political context.  This research is relevant in the increasingly dynamic landscape of contemporary Indonesian art, where artists use visual media to critique socio-political conditions and challenge official narratives through provocative and reflective artistic expressions. The research method employs a qualitative approach using Critical Discourse Analysis (CDA) to examine visual elements such as colour, lines, composition, and discourse related to power symbolism in the paintings. Primary data was obtained through direct observation and literature review of semiotics and Fairclough's critical discourse theory, while secondary data was sourced from exhibition documentation and contemporary art critiques in Indonesia. The findings reveal that Konoha 1 visualises oppressive rulers, reflecting authoritarianism, military dominance, and structural inequality in society. This study affirms that contemporary art is not merely an aesthetic object, but a political actor that facilitates public discourse and drives social change. By placing Konoha 1 within the context of Indonesian critical art, this study highlights how artworks can serve as tools of resistance against authoritarian power structures, while enriching academic discourse on the relationship between art and politics in the era of contemporary democracy.